Water Purification Technology Implementation Design - Anggara Trisna Nugraha; Rahman Arifuddin (Merdeka Malang University, 2020)
Seeing the condition of water availability with good quality which is starting to decrease, it is necessary to have water treatment before the water is suitable for use. Therefore, in this research, a more effective digital measuring instrument is designed to measure water quality in terms of pH and water clarity. The design of tools in the form of natural filtration and pH measuring devices. This study used several water samples, namely rainwater and well water from different locations. Based on the test results, the tool works effectively with a pH value that has been in the standard range from the start (6.5-9) after 4 times of filtration, which is between 6.82-7.60 so that the pH value of the water will be maintained in a condition that is fit for use. . For acidic and alkaline pH categories, it requires repeated processing to get the value according to the standard fit for use